Development And Validation Of An Educational Booklet On Nutrition And Physical Activity For Postpartum Mothers. - Noor Fairuzi Suhana Yahya; Nur Islami Mohd Fahmi Teng; Norsham Juliana Nordin (Fakulti Perubatan dan Sains Kesihatan Universiti Putra Malaysia, 2026)
Indexed by Scopus/MyCite